A histopathological Study of the Oral White Lesion Cases in Benghazi - Amna M Elaboud; Salha A. Zoubi; Ali M. EL- Murtadi (Benghazi University Medical Journal, 2026)
The white lesions of the oral cavity are clinically common. They represent a large number of cases diagnosed as diseases with different severity, such as dysplasia and traumatic keratosis, and may lead to squamous cell carcinoma (SCC). Aim of the study was to determine the types of oral white lesions in all patients who presented to the Oral Pathology Department at the Faculty of Dentistry in Benghazi in the period from 1999 to 2019. Material and methods; This study was a retrospective and descriptive type. The data were taken from the records of 149 cases with white lesions in the oral cavity and squamous cell carcinoma derived from white lesions. Statistical analysis and SPSS program were used. Results; showed that most of the cases were more than forty years old. In general, more women than men were affected. The site of lesion was unilateral buccal mucosa in most cases. More than 56% were diagnosed as lichen planus, followed by leukoplakia (10.7%), simple keratosis (10.7%), frictional hyperkeratosis (6.7%), lichenoid reactions (3.4%), lupus erythematosus (3.4%), and white sponge nevus (2.0%). This study showed that the most common oral lesions, most commonly involved sites, age range and gender predilection were consistent with most published research in the literature, with the possibility of transformation of these lesions into dysplasia and SCC. Conclusion; These lesions were associated with many systemic diseases. Awareness, early diagnosis and treatment will minimize disease further development.